VIOLENCE AND REFINED DISCOURSE IN A GRANDE ARTE, BY RUBEM FONSECA - Reis, Murilo Eduardo dos [UNESP] (2018)
Since the release of his first publication, Rubem Foseca has been associated to a representation of violence through sophisticated language. Such characteristic led Alfredo Bosi to include Fonseca in the brutalist literary movement. This article intends to examine how brutality resulting from social differences in Brazilian society is represented in A grande arte (1983), the second crime novel written by Fonseca. In this novel, the author uses refined narrative techniques to represent in detail situations of explicit violence that involve the protagonist-narrator and other characters and whose main agent for violence is a contract killer. Based on studies about crime novels, Brazilian narrative and narrative techniques, we will reveal the link between the representation of brutality, criticism of social inequality and composition of crime novels achieved through sophisticated writing.